Research methods for the behavioral sciences - Privitera, Gregory J. (Los Angeles Sage, 2020)
"Both comprehensive and clear, Research Methods for the Behavioral Sciences, third edition author Gregory J. Privitera employs a problem-focused approach to introduce research methods. A conversational writing tone speaks to learners directly. While Privitera empowers students to view research methods as something they are capable of understanding and applying. Within each chapter students draw conclusions by following the scientific process. To do enable this Privitera fully integrates the research methods decision tree--from choosing a research design to choosing an appropriate statistic--to encourage students to select the most appropriate methodology for the research question they're seeking to answer. Greg Privitera covers the full scope of methodologies from non-experimental to quasi-experimental to experimental in a straightforward, non-biased manner"--
Includes bibliographical references (549-561 pages) and index.
Keywords: Psychology -- Research -- Methodology; Social sciences -- Research -- Methodology; Psychology -- Statistical methods; Social sciences -- Statistical methods